COVID‐19 response by New Zealand general surgical departments in tertiary metropolitan hospitals. Issue 7 (5th July 2021) - Toh, Karen Hui Qi; Barazanchi, Ahmed; Rajaretnam, Nigel S.; Tan, Jeffrey; Linton, Tara; Murray, Mark; Fagan, Paul; Koea, Jonathan
Abstract: Background: Worldwide, coronavirus disease 2019 (COVID‐19) has significantly challenged the delivery of healthcare. New Zealand (NZ) faced similar potential challenges despite being geographically isolated. Given the rapid change in the COVID‐19 pandemic, hospitals in NZ were tasked with formulating their own COVID‐19 responses based on the Ministry of Health's (MoH) recommendations. Methods: This paper evaluates how six metropolitan general surgical departments in NZ had responded to COVID‐19 in terms of changes made to rosters, theatres, clinics, acute admissions as well as additional measures taken to reduce the risk of staff exposure. It also explores how NZ fared in comparison with international guidelines and recommendations. Data from each centre were provided by an appointed clinician. Results: All centres had adapted new rosters and a restructuring of teams. Handovers, multidisciplinary team meetings and educational sessions were held virtually. Different strategies were implemented to ration hospital resources and reduce the risk of staff exposure. Non‐urgent operations, endoscopies and clinics were deferred with allocation of dedicated COVID‐19 operating theatres. Potential COVID‐19 suspects were screened prior to admission and treated separately. Various admission and imaging pathways were utilised to increase efficiency. Conclusion: General surgical departments in NZ had implemented a comprehensive COVID‐19 response but there is room to work towards a more unified national response. Our analysis shows that these centres across NZ had taken a similar approach which was aligned with international practices. Abstract : This paper looks at how several New Zealand general surgical departments responded to COVID‐19. Data collected focused on changes made to rostering, theatre and clinics allocation, acute admissions in addition to strategies to reduce the risk of staff exposure. We have demonstrated that the New Zealand response is aligned with international recommendation.